An update on the spider genus Loxosceles (Araneae: Sicariidae) in the Afrotropical region, with description of seven new species - Lotz, L. N. (Zootaxa, 2017)
In this paper the present state of knowledge of the genus Loxosceles Heineken & Lowe, 1832 from the Afrotropical region is discussed. The distribution of nine of the 16 described Afrotropical species of Loxosceles is updated and the status of the types of L. bergeri Strand, 1906b and L. pilosa Purcell, 1908 are discussed. A further four new species from South Africa: L. cederbergensis sp. nov.; L. dejagerae sp. nov.; L. haddadi sp. nov.; L. makapanensis sp. nov.; and three from Namibia: L. griffinae sp. nov.; L. irishi sp. nov.; and L. maraisi sp. nov., are described. The female of L. smithi Simon, 1897 is described for the first time. A new taxonomic key to all the Afrotropical species is given.